Stem Cells and Regenerative Medicine: Myth or Reality of the 21th Century - J.-F. Stoltz; N. de Isla; Y. P. Li; D. Bensoussan; L. Zhang; C. Huselstein; Y. Chen; V. Decot; J. Magdalou; N. Li; L. Reppel; Y. He (Stem Cells International)
Since the 1960s and the therapeutic use of hematopoietic stem cells of bone marrow origin, there has been an increasing interest in the study of undifferentiated progenitors that have the ability to proliferate and differentiate into various tissues. Stem cells (SC) with different potency can be isolated and characterised. Despite the promise of embryonic stem cells, in many cases, adult or even fetal stem cells provide a more interesting approach for clinical applications. It is undeniable that mesenchymal stem cells (MSC) from bone marrow, adipose tissue, or Wharton’s Jelly are of potential interest for clinical applications in regenerative medicine because they are easily available without ethical problems for their uses. During the last 10 years, these multipotent cells have generated considerable interest and have particularly been shown to escape to allogeneic immune response and be capable of immunomodulatory activity. These properties may be of a great interest for regenerative medicine. Different clinical applications are under study (cardiac insufficiency, atherosclerosis, stroke, bone and cartilage deterioration, diabetes, urology, liver, ophthalmology, and organ’s reconstruction). This review focuses mainly on tissue and organ regeneration using SC and in particular MSC.